A 3D graphene-based biosensor as an early microcystin-LR screening tool in sources of drinking water supply. (10th May 2017) - Zhang, Wei; Han, Changseok; Jia, Baoping; Saint, Christopher; Nadagouda, Mallikarjuna; Falaras, Polycarpos; Sygellou, Labrini; Vogiazi, Vasileia; Dionysiou, Dionysios D.
Graphical abstract: Highlights: 3D graphene-based biosensors can detect MC-LR with remarkable sensitivity. Good linear correlation between electron-transfer resistance and MC-LR concentration. A detection limit of 0.04 μg/L MC-LR was accomplished. Abstract: Recent advances in graphene synthesis and understanding of properties have led to enormous applications in a variety of areas. Graphene and its unique electrical properties can favor electrochemical biosensor applications for aqueous toxin monitoring. Graphene-based biosensors can be used as an alternative to time-consuming, expensive and non-portable conventional methods of analysis involved in water quality monitoring and assessment. In this work, we showcased a three-dimensional (3D) graphene-based biosensor for microcystin-LR (MC-LR) detection and quantification. We report the efficient functionalization and immobilization of microcystin-LR and its antibodies on the facile synthesized CVD 3D graphene. The modified graphene electrodes were characterized by X-ray photoelectron spectroscopy and micro-Raman spectroscopy. Cyclic voltammetry and electrochemical impedance spectroscopy were used to electrochemically characterize the biochemical events on the electrodes. Specifically, as-prepared 3D graphene-based biosensors can detect MC-LR with remarkable sensitivity due to its macro-porous structure and large surface area, and high conductivity. A very good linear correlation of the electron-transfer resistance ( R 2   =  0.93) was achieved over 0.05 and 20 μg/L MC-LR concentration range. Also, a detection limit of 0.05 μg/L was accomplished, which is much lower than the World Health Organization (WHO) provisional guideline limit of MC-LR concentration (i.e. 1 μg/L) in drinking water.